Pemanfaatan Media Sosial Sebagai Sarana Pemasaran Usaha Mahasiswa Prespektif Maqosid Syariah - Budiyarsih; Fuad Yanuar Akhmad Rifai; Purwanto (Journal of Trends Economics and Accounting Research, 2023)
The use of the internet is currently growing rapidly, making the exchange of information even easier and faster, this is what makes people tend to prefer using the internet for long-distance communication. Social media has many benefits in everyday life, including in the field of business, social media as a means of marketing or promotion of a product so that it can be reached by many consumers, plus this Pandemic period where the government recommends reducing people's activities outside the home so that prevent the spread of Covid-19. Product marketing through social media is very easy and is currently an alternative that people are interested in. The research objective is to find out the use of social media as a means of marketing student businesses in Magelang. Maqasid sharia has the goal of achieving mutual benefit and preventing harm. So that maqasid sharia has policy problems in the field of Islamic economics. In this study using a type of qualitative research by interviewing five business actors run by students in Magelang Regency. The data in this study used primary data, which was conducted by interviewing, documenting and direct observation of business actors.